Effectiveness of Blended Learning Method Through Google Classroom on Learning Independence and Improving Concepts Understanding of Class V Students on Human Digestive System Materials - Rukmi Tri Wahyuni; RM. Teguh Supriyanto; Rif’at Shafwatul Anam (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to analyze the effectiveness of applying the blended learning method in increasing students' conceptual understanding of the human digestive system material and to analyze the effectiveness of science learning using the blended learning method in student independence in the human digestive system material. This research method used a Quasi Experimental Design. The research design consisted of two groups, each of which was randomly selected (R). The first group was given treatment (X) and the other group was not. In research, the group that was given treatment was called the experimental group and the group that was not given treatment was called the control group. The number of respondents in this study amounted to 27 children. This study used the SPSS 21 program with paired sample t-test and independent sample t-test. The results of this study are that the application of the blended learning method in increasing students' conceptual understanding of the material on the human digestive system has been effective, this is evidenced by a significance value of 0.00 <0.05. Science learning with the blended learning method in the independent learning of students in the human digestive system material is very effective, this is evidenced by a significance value of 0.00 <0.05.